2015
DOI: 10.1590/1983-1447.2015.esp.56751
|View full text |Cite
|
Sign up to set email alerts
|

Enfrentando uma experiência difícil mesmo com apoio: a adolescente menor vivenciando a maternagemEnfrentando una experiencia difícil aunque con apoyo: el adolescente menor vivenciando la maternidad

Abstract: RESUMO Objetivos Compreender o significado do cuidar do filho para a mãe adolescente menor, desvelar as demandas para o cuidado e construir um Modelo Teórico sobre essa vivência. Método Pesquisa qualitativa: adotou-se o Interacionismo Simbólico como referencial teórico e a Teoria Fundamentada nos Dados, como metodológico. Participaram do estudo nove mães adolescentes. Técnica de coleta de dados: entrevistas semiestruturadas, realizadas de setembro de 2008 a setembro de 2011, na consulta de enfermagem em pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…The concepts discussed in the 19 selected articles were extracted. The work was compared and grouped by content similarity, in the form of thematic units, being: Transition of roles in society 12,15,18,[21][22][23][26][27] ; Bonding and caring for the child 9-10,12-13,16-18,21, 25 and Teen Mother Support Network 11-15,17-20,23-24 . It aimed to understand the main barriers to feeding and optimal care of infants and young children perceived by adolescents and young women in rural Bangladesh.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The concepts discussed in the 19 selected articles were extracted. The work was compared and grouped by content similarity, in the form of thematic units, being: Transition of roles in society 12,15,18,[21][22][23][26][27] ; Bonding and caring for the child 9-10,12-13,16-18,21, 25 and Teen Mother Support Network 11-15,17-20,23-24 . It aimed to understand the main barriers to feeding and optimal care of infants and young children perceived by adolescents and young women in rural Bangladesh.…”
Section: Methodsmentioning
confidence: 99%
“…23 It is also recognized that intergenerational aspects may influence the relationship between the adolescent mother and the baby. 26 It is observed that some adolescents undergo transformations in their way of being 12 and change of focus in life. 22 It is pointed out, in study, that the interaction with the child triggers positive feelings in the adolescent mother.…”
Section:  Transition Of Roles In Societymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent theoretical model constructed by specialists in early pregnancy/mothering showed that this is a difficult experience even for teenagers who count on social, family and financial support, and stressed that health services should also operate as support networks (17 When health professionals take into consideration the social and cultural context of these young patients, they are more likely to recognize health services as a reference network of support (15). In the present study, this was expressed in the statement of a young woman who recognized the importance of maintaining the pregnant women's groups.…”
Section: In the Groups We Talk To Each Other [] We Feel At Ease Wmentioning
confidence: 99%